Laser shielding and thermal ablation characteristics of resorcinol formaldehyde/boronnitride composites for thermal protection systems - Daniel, Alex; Badhe, Yutika; Srikanth, Ivaturi; Gokhale, Suresh; Balasubramanian, Kandasubramanian (Industrial & Engineering Chemistry Research, 2016)
Resorcinol formaldehyde (RF) composites were modified by incorporating different weight ratios of hexagonal boron nitride (h-BN) through a novel in situ polymerization technique. Temperature modulated SAXS was used to understand the changes in polymer network due to h-BN addition. The ablation performance of RF BN composites was evaluated by pulsed laser and oxyacetylene torch tests. Linear ablation resistance under oxyacetylene conditions improved by 18%. Laser ablation resistance increased by 44%. The reasons for improved ablation resistance for RF BN composites were studied using XRD, FTIR, and XPS methods which indicated that h-BN undergoes phase transformation at higher temperatures and also displays typical floral assimilation leading to significant energy consumption. This results in improved ablation resistance. These findings could lead to fabrication of RF BN based thermal protection systems (TPS) having better protection capabilities.